EUROPEAN GEOSTATIONARY NAVIGATION OVERLAY SERVICE IN UKRAINE - Konin, Valeriy; Shyshkov, Fedir (Proceedings of National Aviation University (archive), 2015)
A research of European Geostationary Navigation Overlay Service (EGNOS) performance was conducted with a help of a satellite navigation receiver, working in the mode of receiving differential corrections. The goal of the research was to define the operation characteristics of EGNOS in central Ukraine, without a ground station. We have estimated the key system parameters, such as: accuracy, availability, continuity and integrity. Using the data recorded by our receiver and PEGASUS software to process it, this article illustrates the current state of EGNOS in Kiev. The research was conducted in static, while having the coordinates of the receiving station calculated in centimeter accuracy. The research was performed under the UKRAINE project, detailed information about the project is given under Acknowledgments header.